A Strengths-Based Group Intervention for Women Who Experienced Child Sexual Abuse. (March 2017) - Walker-Williams, Hayley J.; Fouché, Ansie
Purpose: This study evaluated the benefits of a "survivor to thriver" strengths-based group intervention program to facilitate posttraumatic growth in women survivors of child sexual abuse. Method: A quasi-experimental, one group, pretest, posttest, time-delay design was employed using qualitative methods to evaluate the benefits of the intervention with 10 purposively selected women with a history of child sexual abuse. Six group sessions were conducted as well as a delayed follow-up session. Qualitative data were collected using drawings, narratives, and transcriptions. Results: Qualitative thematic content data analysis portrayed enabling processes of PTG such as emotional awareness, decisive action, posttrauma identity, and a healing group context. Conclusion: These themes suggest growth outcomes. However, a longitudinal study is recommended to establish efficacy and to inform practice with replicable interventions.